Industrial perspective regarding circular economy activities in Atlántico-Colombia - Alvarado-Bawab, María Bernarda; Villa Marenco, Sandra (Economia agro-alimentare/Food Economy - Open Access, 2023)
This work seeks to diagnose the business perspective of the department of Atlántico presenting general strength and weaknesses of companies to undertake circular economy policies; it seeks to know the actions for the circular economy of companies in each sector, the waste generated, resources used and the management systems or methodologies implemented. The results show that minimize waste by recycling or reusing it, in addition of replan and minimize the water consumption are the main actions to implement circular activities; more than a third of companies have at least one quality, security, save or environment management system that circularized its processes a bit; but they do not achieve an economic, social and environmental positive impact. For this reason, these actions need to become in a holistic structure with systematization of practices, focusing on single innovation stages and involving their stakeholders. Besides, in addition of barriers reported by previous studies, the lack of expertise and complex administrative legal procedures are specific gaps for Atlántico Industry applying circular economy processes that should be considered in the model used to implement it. Finally, this work serves as the basis for a future pilot project where the level of success and acceptance of various circular economy methodologies that will be implemented in previously selected companies is compared. In this way, build a relevant method to achieve the culture and capabilities of the industries of the department of Atlántico in order to achieve economic, social and environmental innovation by applying the concept of circular economy.